A neutral mononuclear rhenium(i) complex with a rare in situ-generated triazolyl ligand for the luminescence "turn-on" detection of histidine. Issue 3 (22nd December 2022) - Thanasekaran, Pounraj; Huang, Jui-Hsiang; Jhou, Cing-Rou; Tsao, Hsiang-Chun; Mendiratta, Shruti; Su, Cing-Huei; Liu, Ching-Ping; Liu, Yen-Hsiang; Huang, Jui-Hsien; Lu, Kuang-Lieh
Abstract : A rare in situ -generated mononuclear rhenium complex [Re(bpt)(CO)3 (NH3 )] (1, bpt = 3, 5-bis(2-pyridyl)-1, 2, 4-triazolate) can be used as a "turn-on" luminescent probe for selectively sensing l -histidine against other amino acids. Abstract : A rare in situ -generated mononuclear rhenium complex [Re(bpt)(CO)3 (NH3 )] (1, bpt = 3, 5-bis(2-pyridyl)-1, 2, 4-triazolate) can be used as a "turn-on" luminescent probe for selectively sensing l -histidine against other amino acids. Compound 1 was prepared by reacting Re2 (CO)10, 2-cyanopyridine and hydrazine with an in situ formed bpt ligand through cyclization via C–N and N–N couplings with its single-side chelating mode arrayed with respect to the Re center. Compound 1 was highly stable and showed a green light MLCT emission in DMF solution at 507 nm upon excitation at 360 nm. Interestingly, the emission from 1 could be quenched by the addition of metal ions such as Ni 2+ and Cu 2+ but the emission efficiently recovered with the introduction of histidine. However, histidine could only be selectively detected when a combination of compound 1 and Ni 2+ was used. Therefore, the luminescence response of the Ni 2+ -modified compound 1 could be utilized as a "turn-on" probe for the selective detection of histidine. This work provides a simple method for developing new sensing platforms of a discrete metal complex based on rare in situ generation.